Oral health-related quality of life in patients under supportive periodontal therapy - Sonnenschein, Sarah K.; Betzler, Carlota; Kohnen, Rebecca; Krisam, Johannes; Kim, Ti-Sun (Acta odontologica Scandinavica, 2018)
Objective: To assess the oral health-related quality of life (OH-QoL) in patients under supportive periodontal therapy (SPT) and the influence of the individual periodontal risk as well as different degrees of adherence during SPT on OH-QoL.Materials and methods: 309 patients with at least 5 years of SPT were re-examined. Periodontal risk profile (according to Lang and Tonetti) was assessed and the adherence to SPT-appointments within the last 30(±6) months was reviewed for each patient (fully adherent: adherence to all appointments ±6 weeks, partially adherent: SPT-interval not extended more than half of the recommended interval, insufficiently adherent: SPT-interval extended more than half of the recommended interval, non-adherent: recommended SPT-interval interruption ≥12 months). OH-QoL was measured using the German short-version of the Oral Health Impact Profile (OHIP-G14). Differences between groups (Mann-Whitney U test, Kruskal-Wallis test), association between total OHIP-scores and the predictors age, mean periodontal probing depth and oral hygiene parameters were tested (Spearman’s correlation). A multivariable linear regression model was fitted using all categorical predictors with a univariable p value <.1.Results: Statistical analysis revealed no significant differences in OHIP-G14 scores for gender, periodontal diagnosis and prosthetic status. Patients with deep periodontal pockets (≥6 mm) showed significantly higher OHIP-G14 scores compared to patients without deep pockets (p = .049). Adherence and periodontal surgery were statistically significant predictors for the OHIP-G14 score.Conclusions: OH-QoL of patients under long-term SPT seems to be influenced by periodontal status. Good compliance with SPT-intervals based on the individual periodontal risk profile seems to contribute to a better OH-QoL compared to irregular attendance of SPT.